Evaluation of calcium intakes of young children in the Philippines as a result of the 2008 National Nutrition Survey - Agdeppa, Imelda Angeles; Gironella, Glen Melvin P.; Constantino, Ma. Adrienne S. (2016)
Calcium is considered as the most abundant mineral in the body. Milk and other milk products are the best sources of calcium. Calcium deficiency may lead to osteoporosis. This study was conducted to provide information on dietary calcium intakes of young children as basis for advocacy campaigns on keeping watch on their calcium intakes. A total of 5,691 Filipino children aged 6 months to 10 years old were the respondents in the study. The data were taken from the National Nutrition Survey conducted in 2008. Food intakes were collected by face-to-face interviews using 24-hour food recall questionnaires with mothers of children as respondents. Food intake was transformed to nutrient intakes using the Individual Dietary Evaluation System. The mean one-day calcium intake of young children is 291 mg. There was a declining trend from 6 months to 6 years old and slight increases from 7 to 10 years old. Only 14.8% have met the Estimated Average Requirement for calcium. Milk and milk products contributed to about 33.4% of the total calcium intake. The highest calcium intake of young children came from the richest quintile, compared to the groups belonging to the poorest quintile were intake was lowest. Mean and percent adequacy of calcium intake of children and the consumption of milk as rich source of calcium were both very low.
Keywords: Measurement of calcium in the body; Child nutrition